Kinetics and Mechanism of Reduction in Composite Iron Ore - Reductant Pellets (The Australasian Institute of Mining and Metallurgy, 1999)
A composite iron ore-reductant pellet is a mixture of fine iron ore and fines of coal/char/coke, bonded at essentially room temperature with sufficient green strength for subsequent handling. In ironmaking, these pellets offer the advantage of fast reduction, utilisation of fines, non-coking coal and coke breeze. The composite pellet-based alternative ironmaking processes constitute a promising route for ironmaking in future. The present paper is a brief review of kinetics and mechanism of reduction of iron oxides into iron and other associated reactions, when these pellets are heated to high temperature. It would draw significantly from investigations conducted by the author and his co-workers.